Original Sin Reaffirmed: The Nicaragua Judgement’s Impact on the Notion of Armed Attack as the Most Grave Form of the Use of Force (Polish Yearbook of International Law, 2016)
This article is referenced to the thirtieth anniversary of the ICJ’s Nicaragua judgement on the merits of 1986. It acknowledges the significance of this much-debated judgement for the modern international law on the use of force (jus ad bellum). However the text focuses on one aspect of the judgment only, i.e. the definition of the notion of “armed attack” as the most grave form of the use of force. The impact of the judgement in this respect is critically analysed. It is argued that the introduction to the UN Charter text of undefined notions of the use of force, aggression, and armed attack may be labelled as the “original sin” of contemporary jus ad bellum, as it results in conceptual obscurity. It is also claimed that the ICJ reaffirmed this original sin in its Nicaragua judgment because it explicitly argued for the notion of “armed attack” as the most grave form of the use of armed force and, in consequence, distinguished it from the other, lesser forms of the use of force, while failing to introduce any sort of clarity in the conceptual ambiguity of jus ad bellum. The article also offers some remarks de lege ferenda and suggests abandoning the gravity criterion, which would require abandoning the well-established judicial and doctrinal interpretation approaches to jus ad bellum.